Haploidentical Stem Cell Transplantation for Hematological Disorders: Real-World Experience from India - Mehta, Pallavi; Khushoo, Vishvdeep (South Asian Journal of Cancer, 2023)
Haploidentical transplant (haploSCT) has its own unique complications; hence, we studied the outcome of haploSCT from a cancer hospital in India. We retrospectively analyzed the haploSCTs performed at our center between March 2015 and mid-August 2022 using posttransplant cyclophosphamide (PTCy). Ninety-nine patients (95 malignant and 4 nonmalignant) underwent 101 haploSCTs. Myeloablative (MA), nonmyeloablative (NMA), and reduced intensity conditioning (RIC) were used in 35 (34.6%), 43 (42.5%), and 23 (22.7%) transplants, respectively. The median CD34 +  was 5.9 (1.8–10) ×106/kg. The median time to neutrophil and platelet engraftment was 15 (11–32) and 15.5 (9–120) days, respectively. There were 09 (8.9%) cases of primary graft rejection. Eighteen (17.8%) patients had a relapse. Acute graft versus host disease (GVHD) was observed in 33 (32.6%) cases. Blood cultures were positive in 42 (41.5%) transplants. Common viral infections were BK (47.3%) and cytomegalovirus (CMV; 65.3%). The median follow-up was 6 (0.5–89.5) months. Forty-eight (48.4%) patients had died at the last follow-up. The main causes of the death were sepsis (27 [56.2%]), relapse (10 [22.2%]), and GVHD (04 [8.8%]). The nonrelapse mortality was 37.3%. The median overall survival (OS) was 18 ± 11.46 (0–40.77) months. The 1-year OS was 56.7%, while the 2-year OS was 49.3%. We emphasize that haploSCT offers a reasonable hope of survival for patients, although infections remain a significant challenge based on our experience.
Keywords: hematological disorders; haploidentical transplants; graft versus host disease; relapse; infections; survival